Effect of Charity Rehabilitation Centers on the Welfare of Mentally Disabled Children - Ayda Hosseinkhani (International Journal of Community Based Nursing and Midwifery, 2016)
One of the problems with which mentally challenged children and adolescents are faced in the healthcare systems of the world is that the importance of their problems have often been neglected by decision-makers.1 The problem looks more severe when we investigate health care services to mentally disable children. Generally, a child’s health problem creates an economic burden for families but caring for a child with mental problems affects financial situation of families more as compared to caring for a child with other disorders.2 The available economic resources to provide high quality services for the mentally challenged children are limited. In many countries, mental disorders are a source of fear by people and it might even lead to rejection of the mentally challenged by the community.3 There are many shortcomings in the welfare of children with mental health problems. One of the ways to overcome these shortcomings is involvement of non-governmental organizations(NGOs).3 In many countries, NGOs are in charge of health services in particular areas or among specific populations.4 Their significant part in global health diplomacy shows the emergence of this field.5 The involvement of grassroots communities help is of utmost importance in providing care for the mentally disabled.3 The role of privately funded sectors in providing an alternative to public sector services should be considered as a possible solution for limited resources. There are 10,000 registered NGOs in healthcare fields of activities in Iran.6 The citizens of Fars province have donated approximately thirty eight billion Tomans (Iranian currency), to the health care centers across the province from 2002 to 2005. There are 2 known charity centers in Iran for mentally disabled children, i.e. Shiraz Narjes in Shiraz and Kahrizak in Tehran.3 Although the health care expenditures have been increased rapidly over the past few years in Iran,7 these NGOs continue to provide their services for the disabled. We would like to introduce Shiraz Narjes as an example of the role of NGO in healthcare system for the mentally disabled children in Iran. It provides residential, medical, educational and rehabilitation services to mentally challenged children.This organization was first launched in 1976 as a governmental organization for children with mental problems in Fars province. In 1988, the government of Iran privatized most organizations to stimulate the economy of the country.7 “Shiraz Narjes” became a private institute in 1995 and the main income of this organization from then was provided by grassroots organizations. At this time, they took care of 40 mentally challenged children. In 2000, the county of Fars dedicated the present location to this organization and within 2 years the main buildings were constructed by public donations. This complex includes a residential building, rehabilitation rooms, a laboratory, and a clinic. Today, they deliver services to 212 children with mental disabilities, 44 of whom are male and 168 are female. In this institute, 45 patients are orphans and the others which are 167 patients with families unable to take care of them financially. Most of these children have the intelligence quotient (IQ) score bellow 25 (41.5%) and 33.9% of them show the IQ score between 25 and 50. The daily program for these children includes rehabilitation of patients with psychological, neurological, musculo-skeletal and orthopedic conditions. Higher level of professional therapies such as speech therapy, occupational therapy, and physical therapy are provided to the patients as well if needed. This complex has a clinic; as a result, there is no need to transfer the patients to the hospital for more specialized care. It provides healthcare services to the patients from outside Shiraz Narjes-complex as well. The departments in this clinic include endocrinology, gastroenterology, pediatrics, pediatric gastroenterology, pediatric surgery, general surgery, ENT, cardiology, urology, gynecology, pharmacy, radiology and pathology. The income of the clinic is used to build a second complex for male patients above the age of 14 which will be inaugurated in 2016. Over the past few decades, we have been facing an increase in the number of disabling mental health problems. The economic burden of these diseases is notable among other health expenditures. Considering the existing limitations in our resources, a possible strategic method for providing better health services to these patients is involvement of private sectors and NGOs. In Iran, there are many registered NGOs. Unfortunately, there is lack of scientific evidence of their efficacy. Investigation of the Shiraz Narjes Charity Institute as an NGO showed its sustainable services for 39 years which have been improving over time as to quality and quantity. They have managed to survive regardless of the growing health costs in the country. Despite their efforts, the limited number of patients who could use their services shows the importance of the work which should be performed in the area of NGOs for mentally challenged children in Iran.